2013
DOI: 10.1155/2013/792978
|View full text |Cite
|
Sign up to set email alerts
|

Context-Aware AAL Services through a 3D Sensor-Based Platform

Abstract: The main goal of Ambient Assisted Living solutions is to provide assistive technologies and services in smart environments allowing elderly people to have high quality of life. Since 3D sensing technologies are increasingly investigated as monitoring solution able to outperform traditional approaches, in this work a noninvasive monitoring platform based on 3D sensors is presented providing a wide-range solution suitable in several assisted living scenarios. Detector nodes are managed by low-power embedded PCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…They may be instrumented with accelerometers (Li 2013), piezoelectric sensors (Alwan 2009;Klack et al 2011;Leusmann et al 2011), (capacitive) pressure sensors (Olivier et al 2009;Helal et al 2012;Hoey et al 2011;Stefanov, Bien, and Bang 2004), micro-electro-mechanical systems (MEMS) (Fernandez-Luque et al 2013;Helal et al 2012), or innovative sensors using the near-field imaging principle (reported in Leone, Diraco, and Siciliano 2013), but the solution of a ready-to-be-used pressure-sensitive textile layer (Hanson, Barth, and Silverman 2011;Lauterbach et al 2012), called a presence mat or pressure mat, has been popular since the last years . The same technologies can be used for detecting sofa/bed/chair occupancy (Almudevar et al 2008;Cruz-Sanchez et al 2012;Fernandez-Luque et al 2013;Hilbe et al 2010;Kosse et al 2013;Muñoz et al 2011;Palumbo et al 2014;Suryadevara et al 2013;Raad and Yang 2009;Zhang, Hariz, and Mokhtari 2008).…”
Section: Necessary Evaluation Of the Building Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…They may be instrumented with accelerometers (Li 2013), piezoelectric sensors (Alwan 2009;Klack et al 2011;Leusmann et al 2011), (capacitive) pressure sensors (Olivier et al 2009;Helal et al 2012;Hoey et al 2011;Stefanov, Bien, and Bang 2004), micro-electro-mechanical systems (MEMS) (Fernandez-Luque et al 2013;Helal et al 2012), or innovative sensors using the near-field imaging principle (reported in Leone, Diraco, and Siciliano 2013), but the solution of a ready-to-be-used pressure-sensitive textile layer (Hanson, Barth, and Silverman 2011;Lauterbach et al 2012), called a presence mat or pressure mat, has been popular since the last years . The same technologies can be used for detecting sofa/bed/chair occupancy (Almudevar et al 2008;Cruz-Sanchez et al 2012;Fernandez-Luque et al 2013;Hilbe et al 2010;Kosse et al 2013;Muñoz et al 2011;Palumbo et al 2014;Suryadevara et al 2013;Raad and Yang 2009;Zhang, Hariz, and Mokhtari 2008).…”
Section: Necessary Evaluation Of the Building Environmentmentioning
confidence: 99%
“…The recent topic of augmented reality is mainly supported by the new CV-based fusionsensing device called Kinect (As'ari and Sheikh 2012; Dingli, Attard, and Mamo 2012;Georgoulas, Linner, and Bock 2014;Nishigaki et al 2013). More generally, threedimensional sensing technologies have been thoroughly reviewed by Leone, Diraco, and Siciliano (2013). Among other advantages, they are non-intrusive, and they enable a new vision-based monitoring modality where privacy is preserved since only distance data unable to reveal the subject identity is processed .…”
Section: Identified Trends and Future Solutions For The Building Envimentioning
confidence: 99%
“…Qiang Li et al [ 33 ] investigated a novel fall detection method that utilizes acceleration, posture and context information, where context can be presented by environmental sensors (room location or furniture positions) and personal profiles (e.g., health status and age). A wireless accelerometer, 3-D camera and microphone are simultaneously processed by Leone et al to reach a better result in fall risk assessment [ 34 ]. All the presented studies, however, are lacking a reliable fusing technique, combining processing results from independent components.…”
Section: Related Workmentioning
confidence: 99%
“…In the past decade, with the steady adoption of software solutions and seamless connectivity, electronic health (e-Health) and mobile health (m-Health) have enabled ambient assisted living (AAL) and context-aware scenarios. In this context, real time monitoring and interaction of patients and users with health specialists can be performed remotely [1,2], decreasing overall costs and increasing quality of life, reducing patients displacement, and allowing them to live in their homes [3,4]. Parameters such as biomedical signals, drug distribution, patients' behavior, interactions, and alarm signals can be readily collected and analyzed.…”
Section: Introductionmentioning
confidence: 99%